History in the vernacular - Aquil, Raziuddin; Chatterjee, Partha, 1947- (Ranikhet : Permanent Black ; Bangalore : Distributed by Orient Longman, 2008)
With reference to India; contributed articles.
Includes bibliographical references and index.
Keywords: India -- History -- Historiography